Bactérias anaeróbias oxidadoras de amônio (anammox) aerotolerantes isoladas em sedimentos eutrofizados - Ferreira, Yasmin Girão (2024)
The process of converting ammonium into nitrogen gas (N2), through the action of anaerobic ammonium bacteria (anammox), together with the reduction of nitrite, is an important path for removing nitrogen from wastewater and various natural aquatic ecosystems. This process is widely used in effluent treatment plants to accelerate nitrogen removal. The role of this group of bacteria in natural environments has been studied and understood over the last few years, however, little is still known about their occurrence in aquatic environments in Brazil. Therefore, the present study aimed to detect the presence and isolate aerotolerant anammox bacteria in sediments from eutrophicated aquatic environments. Sediment samples were collected from two aquatic environments in the municipality of Fortaleza (CE): Manguezal de Sabiaguaba (MS) and Açude Santo Anastácio (ASA). Quantitative analyzes of BAA were carried out from these samples, with subsequent isolation, selection and characterization of functional bacteria. Initially, sediment samples were enriched in a selective mineral broth composed to promote the growth of anammox bacteria and incubated in an anaerobic jar for 14 days. After this period, the enriched samples were subjected to serial dilutions, inoculated using the plate technique in petri dishes in solid culture medium selective for anammox and in another non-selective medium (peptone agar), with subsequent incubation in a bacteriological oven at 35oC for up to 5 days. Colony forming units were determined using the Standard Plate Count (SPC) technique. Steps for characterizing the strains individually included: isolation, purification, Gram staining technique, efficiency test for ammonia and nitrite removal, antagonism profiles. Then, bacterial consortia were formed and growth curves were constructed. The genetic detection of anammox activity among bacterial isolates was carried out by amplification of the hzs gene, using the primer pair hzsA_526F/_1857R. Based on this methodological strategy, it was possible to isolate 100 aerotolerant bacteria, including 4 bacteria with anammox activity, in mangrove sediments and an artificial lagoon; assemble 11 anammox consortia efficient in converting nitrogenous compounds in the presence and absence of oxygen, and with effective growth in synthetic effluent. These results are an important contribution to the understanding and future applications of this bacterial group as a technology for treating effluents with high ammonia and nitrite loads.